Classifier constructions as procedural referring expressions in American Sign Language - Jones, Stephen (Research in Language, 2015)
The present paper comments on signs of American Sign Language in the perspective of relevance theory. The main claim is that classifiers encode procedural instructions to help the addressee pick out the intended referent for the procedural referring expressions made with classifier constructions. The author explains how three classes of classifiers differently manipulate concepts to instruct the addressee to create ad hoc concepts though the use of inference, narrowing, and broadening. It is also claimed that classifier constructions do not encode a conceptual meaning, but a procedural instruction. The discussion includes illustrations of how the speaker’s using classifier constructions instead of lexical signs may increase the number of cognitive effects on the part of the addressee.